Digitally enabled affordances for community-driven environmental movement in rural Malaysia - Tim, Yenni; Pan, Shan Ling; Bahri, Shamshul; Fauzi, Ali (Wiley, 2017)
The immense environmental challenges facing society today have necessitated a research effort toward exploring digitally enabled solutions for environmental problems. Only limited research exists today to inform our understanding on how technology could assist groups of individuals in cultivating collective commitment and engaging in actions for environmental sustainability. By presenting an in-depth case study of a social media-enabled grassroots environmental movement in rural Malaysia, this paper aims to illuminate and understand an underresearched phenomenon of community-driven environmental sustainability. This study makes 2 contributions: (1) we draw on the perspective of technology affordances to shed light on both the enabling power and unintended consequences of social media in the pursuit of environmental sustainability; and on that account, (2) we contribute rich, empirically informed insights toward understanding the underresearched phenomenon of digitally enabled, community-driven environmental sustainability.